Exploration of the Dayak Onion (Eleutherine palmifolia (L.) Merr) in the Borderlands of North Kalimantan, Indonesia - Sekarsari, Retno Ayu; Damanhuri, Damanhuri; Kuswanto, Kuswanto (Agro Bali : Agricultural Journal, 2024)
The Dayak onion (Eleutherine palmifolia (L.) Merr) is a plant endemic to Kalimantan, Indonesia, known for its medicinal properties. This study explores the distribution and morphological diversity of Dayak onions in the border areas of North Kalimantan, encompassing Tana Tidung, Bulungan, Malinau Regencies, and Tarakan City. Fifteen unique accessions were collected, and their morphological traits were characterized both qualitatively and quantitatively. The distribution analysis revealed an even spread of Dayak onions across the studied regions. The diversity analysis, using the Shannon-Wiener index, indicated variations in certain quantitative traits like plant height and root length, while qualitative traits like leaf and bulb characteristics remained largely uniform. Principal Component Analysis (PCA) identified key morphological characters contributing to the observed diversity, and cluster analysis revealed kinship relationships among the accessions, with some groups showing high similarity coefficients. This research provides valuable insights into the distribution, diversity, and genetic relationships of Dayak onions in North Kalimantan, contributing to potential agricultural and conservation applications.